Planthopper-Secreted Salivary Disulfide Isomerase Activates Immune Responses in Plants - Fu, Jianmei; Shi, Yu; Wang, Lu; Zhang, Hao; Li, Jing; Fang, Jichao; Ji, Rui (Frontiers in Plant Science, 2021)
The small brown planthopper (Laodelphax striatellus; SBPH) is a piercing-sucking insect that secretes salivary proteins into its plant host during feeding. However, the mechanisms by which these salivary proteins regulate plant defense responses remain poorly understood. Here, we identified the disulfide isomerase (LsPDI1) in the SBPH salivary proteome. LsPDI1 was highly expressed in the SBPH salivary glands and secreted into rice plants during feeding. Transient in planta LsPDI1 expression in the absence of signal peptide induced reactive oxygen species (ROS) burst, cell death, callose deposition, and jasmonic acid (JA) signaling pathway. Deletion mutant analysis revealed that either the a-b-b’ or the b-b’-a’ domains in LsPDI1 are required to induce cell death in plants. LsPDI1 and its orthologs were highly conserved among various planthopper species and strongly induced ROS burst and cell death in plants. Transient in Nicotiana benthamiana LsPDI1 expression impaired the performance of Spodoptera frugiperda and Myzus persicae on host plants. Hence, LsPDI1 is an important salivary elicitor that enhances plant resistance to insects by inducing the calcium, ROS, and JA signaling pathways. The findings of this study provide novel insights into the molecular mechanisms underlying plant-insect interactions.